2021
DOI: 10.1016/j.mayocp.2020.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal and Metabolic Changes of Aging and the Influence of Lifestyle Modifications

Abstract: Increased life expectancy combined with the aging baby boomer generation has resulted in an unprecedented global expansion of the elderly population. The growing population of older adults and increased rate of age-related chronic illness has caused a substantial socioeconomic burden. The gradual and progressive age-related decline in hormone production and action has a detrimental impact on human health by increasing risk for chronic disease and reducing life span. This article reviews the age-related decline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 300 publications
0
38
0
Order By: Relevance
“…The differentiation between physiological adjustments that can be beneficial to the aging process, from changes that are considered to be the main alterations in the development of metabolic complications and chronic diseases associated with the elderly, is necessary. This distinction is needed mostly to develop medical interventions targeted to specific hormone disorders to achieve longevity and a better quality of life [6,8].…”
Section: Endocrine Changes In the Elderly Subjectmentioning
confidence: 99%
See 2 more Smart Citations
“…The differentiation between physiological adjustments that can be beneficial to the aging process, from changes that are considered to be the main alterations in the development of metabolic complications and chronic diseases associated with the elderly, is necessary. This distinction is needed mostly to develop medical interventions targeted to specific hormone disorders to achieve longevity and a better quality of life [6,8].…”
Section: Endocrine Changes In the Elderly Subjectmentioning
confidence: 99%
“…Interestingly, these complex alterations in hormonal networks are related to the decline in physiologic functions and the onset of chronic diseases such as frailty, sarcopenia, osteoporosis, obesity, hypertension, diabetes, hyperlipidemia, atherosclerosis, and immune functions reduction. (Table 1) Additionally, these endocrine alterations are prevalent in patients that develop degenerative brain disease with cognitive impairment and a general decline in brain function [6].…”
Section: Endocrine Changes In the Elderly Subjectmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this increased susceptibility could be reduced by adequately addressing specific risk factors [ 6 ]. Aging is associated with a number of physiological changes including metabolic dysregulation, cognitive decline, vascular alterations, and changes in hormone production [ 7 , 8 , 9 , 10 ]. In addition, aging is accompanied by complex changes and dysfunction of the immune system, leading to an increase in the concentration of inflammatory markers in the blood, a phenomenon known as “inflammaging” [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this clinical study ERT was shown to significantly reduce wound size, increase collagen deposition, and improve wound stiffness. Further beneficial effects of ERT in elderly women involve reduced risk of bone fracture, colorectal cancer, and incidence of menopausal symptoms [9,10]. However, reported…”
Section: Introductionmentioning
confidence: 99%